THEMATIC AND VISUAL ANALYSIS OF THE SHORT FILM “MANIPULATOR” AS A FORM OF COMMENTARY ON SOCIAL DYNAMICS - Putu Eka Kharisma Dewi; Peter Wayan Minheere; Putu Chrisma Dewi; Putu Chris Susanto (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2022)
ABSTRAKThe purpose of this study is to analyze how short films may become forms of media that raise and comment on controversial issues in society. The authors used descriptive analysis to analyze an Indonesian short film titled "Manipulator" by Ferry Irwandi using thematic and visual analysis, in determining whether and how short films and the development of characters within the film, can serve as a form of commentary or even criticism on social dynamics occurring in society. The short film provides an overview of how social dynamics occur through the role of everyone in a community depicted through the game "Werewolf”.Keywords: short film, social role, community, thematic analysis, visual analysis